Swot Analysis of Strategies for Agricultural Entrepreneurs Empowerment - Shohreh Karami; Hossein Agahi (International Journal of Agricultural Management and Development, 2018)
The purpose of this study was to identify strategies for agricultural entrepreneurs empowerment in Javanrod, Salasebabajani, Ravansar and Paveh counties of Kermanshah Province. The structural impact obtained was based on different qualitative techniques and was analysed based on the SWOT model. The finding suggested that the most effective strengths were: adoption of social responsibilities increasing with weighted score "0.305", knowledge, attitudes and values increasing in the agricultural entrepreneurs with weighted score "0.300"; the most effective weaknesses were: lack of enough capital with weighted score "0.260", lack of entrepreneurial culture with weighted score "0.208"; the most effective opportunities were: supporting ideas and projects with weighted score "0.330", entrepreneurial skills trading (the capacity to identify opportunities, problems and solutions) with weighted score "0.315", and the most effective threats were: lack of economic security "0.265" and suitable market lack for products "0.250". The results suggested that by aggressive strategies such as training and entrepreneurial skills development and technical, knowing the sources of ideas, using new technologies, increasing access to training and funds, access to commercial networks, creating exhibitions and conferences application; adaptive strategy promoting use of banking facilities; contingency strategies such as reducing the threat of being able to create diverse career opportunities, reducing administrative bureaucracy, difficulty in getting a licence and infrastructure to create suitable market production; defence strategy including reduction of threats such as economic insecurity can be used as background empowerment entrepreneurs for agricultural entrepreneurs empowerment.